Visualising COVID‐19: Implications for Design Education. - Chatteur, Fiona; Leppens, Mieke (International Journal of Art & Design Education, 2023)
This paper reports on the findings of a visual text analysis of selected infographics and data visualisations used in news websites during the COVID‐19 pandemic in Sydney, Australia. Infographics and data visualisations used in news website articles disseminated and communicated local and national information to the public about the COVID‐19 pandemic and related social implications. For the first time live data, animation and interaction were used in reporting health and societal information to a general news readership, contributing to the knowledge base and visual literacy of the public. The information presented was not only clear but also aesthetically appealing. This paper examines the styles of news digital infographics and data visualisation of three longitudinal studies using lessons learned from Grainger et al. (2016), Dick (2020) and Tufte (2001) and contextualises the context, narrative, aesthetics, communication, data, functionality and examines the collaboration between communication designers, journalists and the development team. The implications for communication design education are explored in the context of skills, tools and teamwork needed for future communication design students.